Social Protests in Brazil: Between the Crisis of Progressive Governments and the Rise of the Right, 2014-2018 - Quiroga, María Virginia (2020)
The  aim  of  this  article  is  to  examine  the  characteristics  and  transformations  of  social protest in Brazil throughout the latest years of the Partido dos Trabalhadores governments  and  Jair  Bolsonaro's  rise  to  the  presidency.  From  a  qualitative  approach, we analyze the experiences of Movimento Brasil Livre (MBL) and Vem Pra Rua (VPR), which carried out some of the most significant collective actions since 2014 and were explicitly articulated with political actors. In this study we try to identify who are the participants of these movements, which are their repertories of action and why they choose to participate in social mobilizations. We are also interested  in  recognizing  their  perspectives  regarding  politics  and  governments.  This exploration will contribute, not only to understand some of the features that collective action presents in this particular context, but also it will offer relevant analytical keys to understand recent political turns in Brazil.